Kosmologi dalam Perspektif Tafsir Izwaji - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
The cosmology of a study that develops with the disposition and development of the universe, which is a system of natural and orderly change that is a creation of God, shows His Oneness (sunatullah). Cosmology covers the changes in human life derived from water undergoing changes into germs, 'alaqah, mudghah, growing into human form expands the species until it alternates continuously. The preaching of human behavior is driven by intentions (motivations) derived from the nature of man who is His creation. He it is Who created the night and the day, and the sun and the moon, each rising up so that you may take heed. The change of vegetation derived from seeds (seeds) grows into grains that grow into vegetation.